2014
DOI: 10.1063/1.4898802
|View full text |Cite
|
Sign up to set email alerts
|

Microwave remote plasma enhanced-atomic layer deposition system with multicusp confinement chamber

Abstract: A microwave remote Plasma Enhanced-Atomic Layer Deposition system with multicusp confinement chamber is established at the Plasma and Beam Physics research facilities, Chiang Mai, Thailand. The system produces highly-reactive plasma species in order to enhance the deposition process of thin films. The addition of the multicusp magnetic fields further improves the plasma density and uniformity in the reaction chamber. Thus, the system is more favorable to temperature-sensitive substrates when heating becomes un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A previous study showed that 3 nm thick Al 2 O 3 film has a low atomic concentration of Al of about 5%. Thus, after 370 cycles, the thickness of the Al 2 O 3 film on ODPA was probably less than 3 nm . Compared to the approximately 60 nm thickness of Al 2 O 3 on Ti substrate, the newly developed AS-ALD process effectively blocked the deposition of the ALD Al 2 O 3 film on the ODPA surface over 370 cycles of ALD.…”
Section: Resultsmentioning
confidence: 97%
“…A previous study showed that 3 nm thick Al 2 O 3 film has a low atomic concentration of Al of about 5%. Thus, after 370 cycles, the thickness of the Al 2 O 3 film on ODPA was probably less than 3 nm . Compared to the approximately 60 nm thickness of Al 2 O 3 on Ti substrate, the newly developed AS-ALD process effectively blocked the deposition of the ALD Al 2 O 3 film on the ODPA surface over 370 cycles of ALD.…”
Section: Resultsmentioning
confidence: 97%